PRELIMINARY STUDY ON RELAP5 SIMULATION OF DVI LINE BREAK ACCIDENT IN THE ATLAS FACILITY USING BEST ESTIMATE PLUS UNCERTAINTY METHOD - Ekariansyah, Andi Sofrany; Widodo, Surip (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2017)
The Best Estimate plus Uncertainty (BEPU) is a methodology, which was introduced in the deterministic safety analysis to evaluate limitations of codes in simulating realistic plant behavior by providing quantified uncertainty bands of calculation results. It has been already widely accepted in licensing nuclear power plant by regulatory bodies of United States (USNRC), Argentina, and Canada. The uncertainty evaluation in the BEPU method is performed by different approaches such as GRS, IRSN, ENUSA, AEAT, and UNIPI. Due to the complexity of other approaches, the purpose of this study is to present some key aspects of the BEPU process using the GRS methodology by selecting the ATLAS test facility to simulate 50% break of DVI line since any safety analysis performed so far was using deterministic best estimate approach only. As comparison of the best estimate simulation performed by RELAP5/SCDAP/Mod3.4, experimental data related to the event was used. After 100 simulations, the uncertainty bands of peak heater of clad temperature and primary pressure transient obtained were only in a close agreement with the experimental data in the earlier period and less than 250 seconds during the transient condition. Therefore the overall accuracy of the best estimate simulation plays a key role on the final results of the uncertainty analysis because the propagation of any discrepancy in the best estimate with the experimental data will occur throughout the simulation. After that, selecting the important parameters to be randomly generated needs to be performed carefully by studying the important phenomena related to the event analyzed and associated plant model.